Osmoregulatory response of Rutilus frisii kutum fingerlings to saline conditions - Hosseini, Seyedali (2013)
This study was carried out to determine the appropriate weight (smolt) of hatcheryreared Rutilus frisii kutum (Kamenskiy, 1901) and a suitable salinity for releasing fingerlings into the natural habitat. For this, important factors such as osmoregulatory hormones, level of serum osmotic pressure, Na+/K+ ATPase, blood ions, gill chloride cells activity and chloride cell size were investigated. In the study, 454 fingerling were allocated into four weight groups namely 1, 3, 5 and 7 g and exposed to three salinity treatments i.e. Caspian sea water (12-13 ppt), estuarine water (7-9 ppt) and Freshwater (control, 0.3 ppt). Each trial was run with three replicates and the experiments were laid out in a randomized complete block design (RCBD). In order to determine the ionic/osmoregulation ability, the blood samples and tissue fixations were carried out during 0, 12, 24, 48, 144 and 336 hours after exposure in the different salinities. Plasma osmolarity was measured using osmometer, blood Na+ and K+ concentrations were estimated by flame photometer, auto-analyzer (RA1000) was employed to measure the Mg2+ and Cl- concentration with colorimetric methods. On the other hand, blood cortisol and prolactin level were determined by RIA (radioimmunoassay) and a competitive ELISA method, respectively. Na+/K+-ATPase activity in homogenates of gills was studied through phosphate released from ATP. Histological indicators including chloride cell perimeter and area were assessed using Biocom software and light microscope with digital camera. The results of osmolarity and ions measurement showed that 3, 5 and 7 g kutum (Rutilus frisii kutum) could maintain the osmolarity and ion concentrations and adapt to salinity of 7 and 13 ppt. However, the level of cortisol and prolactin in 1 g kutum after 48 hours up to the end of the experiment showed significantly higher values compared to other weight groups (P<0.05). The size of chloride cells did not change in 1 g kutum in different salinities. However, in other groups, a significant increase of this perimeter was detected during the experiments (P<0.05). The Na+/K+ ATPase activities in 3, 5, and 7 g weight groups, under exposure to 7 and 13 ppt salinities, were seen to be higher than 1 g juvenile kutum and respective control level (P<0.05). In conclusion, the current research finding indicated that ionic/osmoregulatory ability of juvenile kutum depends on their body weights. Despite, high ability of sea water adaptation in 3, 5 and 7 g kutum, 1 g fingerlings were not able to adapt themselves to the Caspian Sea and estuarine water as well as other groups. Therefore, they cannot be considered as the suitable weight for the release process and net-culture in Caspian Sea water salinity.